Transforming Heritage: Analyzing Cultural Capital and Value Shifts in Indonesia's Ngunjung Buyut Tradition - Arief, Dwi; Komariah, Siti; Wulandari, Puspita (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Social change and modernization have impacted various traditions in Indonesia, including Ngunjung Buyut, an ancestral homage tradition that holds significant meaning for the Indramayu community, West Java. In the context of changing times, this tradition has undergone a shift in values. This research employs a qualitative approach with a case study method conducted in Penganjang Village, Indramayu Regency. Data collection was carried out through in-depth interviews and participatory observation involving informants from both older and younger generations. Data analysis focuses on identifying forms of cultural capital that have emerged within the Ngunjung Buyut tradition in the contemporary era. Findings indicate that objectified cultural capital, such as ngarak processions and artistic performances, has become the primary attraction for younger participants, shifting the focus away from religious activities like communal prayer. While these supporting activities have successfully increased youth engagement, this shift poses a risk to the internalization of religious values. Additionally, this transformation has created a new dynamic in social solidarity, where recreational aspects now overshadow the tradition’s original spiritual significance. Perubahan sosial dan modernisasi telah memengaruhi berbagai tradisi di Indonesia, termasuk Ngunjung Buyut, tradisi penghormatan leluhur yang penting bagi masyarakat Indramayu, Jawa Barat. Dalam konteks perkembangan zaman, tradisi ini mengalami pergeseran nilai. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di Desa Penganjang, Kabupaten Indramayu. Pengumpulan data dilakukan melalui wawancara mendalam dan observasi partisipatif yang melibatkan informan dari golongan tua dan muda. Analisis data berfokus pada identifikasi bentuk modal budaya yang terbentuk dalam tradisi Ngunjung Buyut di era sekarang. Hasil penelitian menunjukkan bahwa objectified cultural capital, seperti kegiatan ngarak dan pertunjukan seni, kini menjadi daya tarik utama bagi generasi muda, menggeser fokus dari kegiatan religius seperti doa bersama. Meskipun kegiatan pendukung berhasil meningkatkan partisipasi generasi muda, pergeseran ini menimbulkan risiko berkurangnya internalisasi nilai keagamaan. Selain itu, perubahan ini juga menciptakan dinamika baru dalam solidaritas sosial, di mana aspek rekreatif lebih menonjol dibandingkan dengan makna spiritual awal tradisi.